Bacterial flagellin is a dominant, stable innate immune activator in the gastrointestinal contents of mice and rats. (31st December 2023) - Vijay-Kumar, Matam; Bovilla, Venugopal R.; Yeoh, Beng San; Golonka, Rachel M.; Saha, Piu; Joe, Bina; Gewirtz, Andrew T.
ABSTRACT: Intestinal contents comprise the largest repository of immunogenic ligands of microbial origin. We undertook this study to assess the predominant microbe-associated molecular patterns (MAMPs) present therein and the receptors) that mediate the innate immune responses to them. Here, we demonstrated that intestinal contents from conventional, but not germ-free, mice and rats triggered robust innate immune responses in vitro and in vivo . Such immune responses were abrogated in the absence of either myeloid differentiation factor 88 (MyD88) or Toll-like receptor (TLR) 5, but not TLR4, suggesting that the stimuli was flagellin ( i.e ., protein subunit of flagella that drives bacterial motility). Accordingly, pre-treating intestinal extracts with proteinase, thereby degrading flagellin, was sufficient to block their ability to activate innate immune responses. Taken together, this work serves to underscore flagellin as a major, heat-stable and bioactive MAMP in the intestinal content that confers this milieu strong potential to trigger innate immune responses.